The old lion : a novel of Theodore Roosevelt [large type] - Shaara, Jeff, 1952- (Thorndike Press large print historical fiction., 2023)
"From the mid-nineteenth century to the early twentieth century, from the waning days of the rugged frontier of a young country to the emergence of a modern, industrial nation exerting its power on the world stage, Theodore Roosevelt embodied both the myth and reality of the country he loved and led. From his upbringing in the rarefied air of New York society of the late 19th century to his time in rough-and-tumble world of the Badlands in the Dakotas, from his rise from political obscurity to Assistant Secretary of the Navy, from national hero as the leader of the Rough Riders in the Spanish-American War to his accidental rise to the Presidency itself, Roosevelt embodied the complex, often contradictory, image of America itself. In gripping prose, Shaara tells the story of the man who both defined and created the modern United States" --